AN ANALYSIS OF PERSONAL AND COLLECTIVE TRAUMA IN KHALED HOSSEINI’S NOVEL SEA PRAYER - Laila Shoukat; Sanah Waheed; Khushnood Arshad (JEE (Journal of English Education), 2021)
This research study is an attempt to explore the literary text of "Sea Prayer" written by Khaled Hosseini with the perspective of trauma study that includes personal trauma model of Cathy Caruth and collective trauma model of Kia Erikson. The theoretical framework focuses on both i.e., Caruth (1996) personal trauma discussed in "Unclaimed Experience: trauma, narrative and history" and Erikson (1991) collective trauma discussed in "Notes on Trauma and Community". This research study examines the elements of personal trauma of the Narrator's character through flashbacks, timelessness and unspeakablity. On the other hand, the elements of collective trauma are also investigated that are breakage of communal bond, distrust in future, mood of fear and depression on the collective level. In addition, the method used is the qualitative analysis. Through aforementioned elements, the researcher has discussed the collective trauma of Syrian community as a whole. Keywords: Trauma, Sea Prayer, textual analysis, Cathy Caruth.